Effects of Exercise Training during Christmas on Body Weight and Cardiometabolic Health in Overweight Individuals - Ramirez-Jimenez, Miguel (Int J Environ Res Public Health, 2020)
Individuals with abdominal obesity and metabolic syndrome (MetS) have augmented risk of all-cause mortality. Lifestyle interventions are effective to treat MetS, however, there are periods during the year in which exercise programs are discontinued and improper dietary habits reappear (e.g., Christmas holidays). We aimed to analyze if exercise-training during Christmas holidays would avoid body-weight gains and cardiometabolic deterioration in MetS individuals, using a randomized control trial. Thirty-eight men with MetS undergoing exercise training were randomly allocated to either continue (TRAIN group, n = 16) or discontinue (HOLID group, n = 22) training, during the three weeks of Christmas. Anthropometrics (body weight, fat, and waist circumference), fasting blood metabolites (glucose, insulin, triglycerides, and cholesterol concentrations) and exercise maximal fat oxidation (FO(MAX)) and oxygen uptake (VO(2PEAK)) were determined before and after Christmas. Both groups were similar at baseline in all parameters (p > 0.05). HOLID group increased body weight (91.3 ± 13.0 to 92.0 ± 13.4 kg, p = 0.004), mean arterial pressure (94.0 ± 10.6 to 97.1 ± 8.9 mmHg, p = 0.026), blood insulin (10.2 ± 3.8 to 12.5 ± 5.4 µIU·mL(−1), p = 0.003) and HOMA (3.2 ± 1.3 to 4.1 ± 2.3, p = 0.003). In contrast, TRAIN prevented those disarrangements and reduced total (170.6 ± 30.6 to 161.3 ± 31.3 mg·dL(−1), p = 0.026) and low-density lipoprotein cholesterol (i.e., LDL-(C), 104.8 ± 26.1 to 95.6 ± 21.7 mg·dL(−1), p = 0.013). TRAIN also prevented the reductions in exercise FO(MAX) and VO(2PEAK) that was observed in the HOLID group (p = 0.002). In conclusion, exercise training during Christmas, prevents body weight gains and the associated cardiovascular (increase in blood pressure and LDL(-C)) and metabolic (reduced insulin sensitivity) health risks are an optimal non-pharmacological therapy for that period of the year.